2020
DOI: 10.3389/fpsyt.2020.00168
|View full text |Cite
|
Sign up to set email alerts
|

Workplace-Related Interpersonal Group Psychotherapy to Improve Life at Work in Individuals With Major Depressive Disorders: A Randomized Interventional Pilot Study

Abstract: Objectives: Individuals suffering from major depressive disorder (MDD) often report workplace-related stress as the major cause of their disorder. Accordingly, workplacerelated stress was established as a fifth psychosocial problem area of Interpersonal Psychotherapy (workplace-related Interpersonal Psychotherapy, W-IPT). The aim of the study was to investigate the influence of W-IPT on depressive symptoms and on workplace-related issues in individuals with MDD compared to a treatment-as-usual (TAU) condition.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 54 publications
0
15
0
1
Order By: Relevance
“…Concepts of work-related psychotherapy were most often developed to support vocational reintegration of employees being sick-listed due to CMDs, including - inter alia - work-related assessments, assistance in drawing RTW plans and contacting employers and occupational physicians as well as evaluation of RTW steps [ 19 24 ]. However, work-related psychotherapy could also contribute to reduction of depressive symptoms and improvement of work ability at earlier stages [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Concepts of work-related psychotherapy were most often developed to support vocational reintegration of employees being sick-listed due to CMDs, including - inter alia - work-related assessments, assistance in drawing RTW plans and contacting employers and occupational physicians as well as evaluation of RTW steps [ 19 24 ]. However, work-related psychotherapy could also contribute to reduction of depressive symptoms and improvement of work ability at earlier stages [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…As noted above, IPT is a treatment that deals with social support itself, so improving symptoms with IPT and restoring social function may be of constant relevance. Reports on IPT that compared treatment as usual (TAU) and group sessions of workplace-related interpersonal psychotherapy (W-IPT) among 27 depression patients have shown that it has significant effects on depressive symptoms as well as in subjective work performance, self-efficacy to return to work, and insomnia (18). A randomized trial that compared eight sessions of W-IPT and TAU in 28 patients with depression exhibited significant improvements and the effectiveness of W-IPT in reducing depressive symptoms, work-ability (WAI), return-towork attitude (RTW-SE), and the effort-reward ratio (ERI) (19).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, he concluded that most probably he was having a mental problem, i.e., a depressive episode. He realized that something needed to change, and that is why took part in our W-IPT study [ 33 ].…”
Section: Case Descriptionmentioning
confidence: 99%
“…Bob was able to adapt. According to him, he profited most from the communication of the Kiesler Cirumplex model [ 33 , 35 ]. Moreover, it helped him to be aware of his self-awareness and self-care.…”
Section: Case Descriptionmentioning
confidence: 99%
See 1 more Smart Citation